Effect of Benzoic Acid Feeding Strategy on Weanling Pig Growth Performance and Fecal Dry Matter - Katelyn N. Gaffield; Joel M. DeRouchey; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 350 weanling barrows (DNA 200 × 400, DNA; initially 13.0 ± 0.08 lb) were used in a 38-d study to evaluate the effects of different benzoic acid feeding strategies on nursery growth performance and fecal dry matter. Pigs were randomly assigned to pens (5 pigs per pen) and pens were allotted to 1 of 5 dietary treatments with 14 pens per treatment. Diets were fed in 3 phases: phase 1 from weaning to d 10, phase 2 from d 10 to 18, and phase 3 from d 18 to 38. Dietary treatments were formulated to provide 0, 0.25, or 0.50% benzoic acid (VevoVitall, DSM Nutritional Products, Parsippany, NJ) added at the expense of corn. Treatment 1 served as the control without benzoic acid throughout all three dietary phases. Inversely, treatment 2 included 0.50% benzoic acid throughout all three phases. Treatment 3 contained 0.50% benzoic acid for phase 1 and phase 2, and 0.25% benzoic acid in phase 3. Treatment 4 contained 0.50% benzoic acid for phase 1 and phase 2, but no benzoic acid in phase 3. Finally, treatment 5 contained 0.50% benzoic acid in phase 1, 0.25% benzoic acid in phase 2, and no benzoic acid in phase 3. From d 0 to 10 (phase 1), pigs fed 0.50% benzoic acid had increased (P= 0.034) ADG, improved (P= 0.049) F/G, and were heavier (P= 0.040) on d 10 than those fed the control diet. From d 10 to 18 (phase 2), pigs fed 0.50% benzoic acid had increased (P<0.01) ADG compared to pigs fed either none or 0.25% benzoic acid, while pigs fed 0.25% benzoic acid had poorer (P<0.001) feed efficiency compared to pigs fed 0 or 0.50% benzoic acid. From d 18 to 38 (phase 3), pigs fed 0.50% and 0.25% benzoic acid had increased (P<0.01) ADG and ADFI compared with pigs fed no benzoic acid. For the overall experimental period (d 0 to 38), pigs fed 0.50% in the first two phases and 0.25% benzoic acid in the final phase had a greater (P<0.05) ADG than pigs fed no benzoic acid through all three phases, or pigs fed 0.50% in the first two phases and no benzoic acid in the final phase, with the other treatments intermediate. Additionally, pigs fed 0.50% in the first two phases and 0.25% benzoic acid in the final phase had improved (P<0.05) F/G compared with pigs fed no benzoic acid throughout all three phases, pigs fed 0.50% in the first two phases and no benzoic acid in the third phase, or pigs fed 0.50%, 0.25%, and no benzoic acid, respectively. There was no evidence for differences (P>0.10) in fecal DM among treatments for samples collected on d 10 or d 18. These data suggests that nursery pigs fed benzoic acid had improved growth performance compared to control pigs. However, when the benzoic acid was removed from the diet before the end of the nursery phase, the pigs experienced a reduction in performance which resulted in similar overall nursery performance to the control diet without benzoic acid.
Keywords: acidifier; nursery pigs; growth performance; benzoic acid